260 A Single Centre Retrospective Study of Cytogenetic Profile, Management and Outcome of Acute Myeloid Leukaemia in Children. (October 2012) - O'Hare, P; Taj, M; Lancaster, D
Abstract : Background and Aims: AML15 was the first major trial to compare anthracycline based consolidation to a Cytosine-Arabinoside based one. Following closure of the trial, standard therapy of cytosine - arabinoside consolidation therapy is currently recommended at this centre. A review of the cytogenetic, treatment and outcome profiles for patients diagnosed with Acute Myeloid Leukaemia was undertaken following concerns regarding relapse rates. Methods: A retrospective study was conducted at the Royal Marsden Hospital on children (aged less than 18), diagnosed to have acute Myeloid Leukaemia between January 2004 and June 2011. Results: A total of 72 patients were identified, of which 7 patients did not achieve remission following induction chemotherapy with ADE. 48 patients were appropriate for comparison, 22 patients received treatment with cytosine - arabinoside (ara-C) based consolidation and 26 patients received treatment with anthracycline based therapy (MACE/MIDAC). 9 patients (41%) in the araC group relapsed and 3 of these patients subsequently died. In only 1 patient this was secondary to resistant disease. Of the 9 patients who relapsed 6 had adverse cytogenetics. Within the group of patients treated with MACE/MIDAC consolidation, 14 relapsed (54%) and of these, 10 patients subsequently died. 6 of the 14 relapsed patients had adverse cytogenetic profiles. No patient within the MACE/MIDAC group had treatment changed due to cardiotoxicity. Chi-squared analysis of death rates identified a p value < 0.1, but more than 0.05. Conclusions: The outcome analysis indicates that there is no significant difference between rates of relapse or death in the 2 groups of patients.